2020
DOI: 10.1103/physrevd.101.064048
|View full text |Cite
|
Sign up to set email alerts
|

Weak cosmic censorship conjecture for a Kerr-Taub-NUT black hole with a test scalar field and particle

Abstract: Motivated by the recent researches of black holes with NUT charge, we investigate the validity of the weak cosmic censorship conjecture for Kerr-Taub-NUT black hole with a test massive scalar field and a test particle, respectively. For the scalar field scattering gedanken experiment, we consider an infinitesimal time interval process. The result shows that both extremal and near-extremal Kerr-Taub-NUT black holes cannot be over-spun. For the test particle thought experiment, the study suggests that extremal K… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 96 publications
(113 reference statements)
1
25
0
Order By: Relevance
“…In past several decades, based on Wald's gedanken experiment, many significant works have been done to check this conjecture. Some of them have indeed proved its validity under certain conditions [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], while the others attempt to present its violations [22][23][24][25][26]. Besides, other various possible examples to violate cosmic censorship are also proposed.…”
Section: Introductionmentioning
confidence: 98%
“…In past several decades, based on Wald's gedanken experiment, many significant works have been done to check this conjecture. Some of them have indeed proved its validity under certain conditions [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], while the others attempt to present its violations [22][23][24][25][26]. Besides, other various possible examples to violate cosmic censorship are also proposed.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, Gwak divided the scattering process into a series of infinitesimal time interval and considered an infinitesimal process only, the result shows that Kerr-(anti) de Sitter black holes cannot be overspun by a test scalar field [58], and many works have been done following this line [59][60][61][62][63]. The dividing of infinitesimal time interval process may provide clues that time interval for particles crossing the event horizon may be important for considering the weak cosmic censorship conjecture [64][65][66]. For other works to destroy the horizon of a black hole, see Refs.…”
Section: Introductionmentioning
confidence: 99%
“…The perturbation of Kerr-Newman black holes by neutrino fields violates the null energy condition, thus could lead to over-spinning of Kerr-Newman black holes [64,65]. In [66], it was found that test scalar field cannot overspin a Kerr-Taub-NUT black hole, but near extremal one can be overspun with test particle. The authors suggested that the different results between test field and test particle indicate the time interval for particles crossing the black hole horizon is important.…”
Section: Examples and Counterexamples To Cosmic Censorshipmentioning
confidence: 99%